An evolutionary life history approach to understanding mental health. Issue 6 (1st October 2020) - Han, Wen; Chen, Bin-Bin
Abstract : In recent years, evolutionary life history theory has been used as a heuristic framework to understand mental health. This article reviews the life history theory and its integration with mental disorders and then introduces representative research methods and related empirical studies in the field of evolutionary psychopathology. In the end, this article concludes with future directions for further research examining and developing the evolutionary psychopathological framework.